1997
DOI: 10.1002/(sici)1097-4644(199701)64:1<128::aid-jcb15>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in bone formation, osteoblastic cell proliferation, and differentiation during postnatal osteogenesis in human calvaria

Abstract: We have determined the age-related changes in the growth characteristics and expression of the osteoblast phenotype in human calvaria osteoblastic cells in relation with histologic indices of bone formation during postnatal calvaria osteogenesis. Histomorphometric analysis of normal calvaria samples obtained from 36 children, aged 3 to 18 months, showed an age-related decrease in the extent of bone surface covered with osteoblasts and newly synthesized collagen, demonstrating a progressive decline in bone form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…an increase of vascular porosity) with age is also shown in [46] authors determined microstructural and strength variables of the distal radius of healthy girls by high-resolution peripheral computerized tomography and micro-finite element analysis and quantified low trabecular vBMD and thickness in the distal radius associated with reduced bone strength and increased fracture risk during growth. The aforementioned increase of vascular porosity is also consistent with the decrease of bone formation with increased age between 3 and 18 months, as evidenced by de Pollak et al [47] in terms of histomorphometric indices.…”
Section: Discussionsupporting
confidence: 86%
“…an increase of vascular porosity) with age is also shown in [46] authors determined microstructural and strength variables of the distal radius of healthy girls by high-resolution peripheral computerized tomography and micro-finite element analysis and quantified low trabecular vBMD and thickness in the distal radius associated with reduced bone strength and increased fracture risk during growth. The aforementioned increase of vascular porosity is also consistent with the decrease of bone formation with increased age between 3 and 18 months, as evidenced by de Pollak et al [47] in terms of histomorphometric indices.…”
Section: Discussionsupporting
confidence: 86%
“…Sites of osteoblast-mediated bone modeling can be readily identified by the presence of mature cuboidal osteoblasts lining bone surfaces and verified by demonstrating that these osteoblasts express the bone matrix protein type I collagen (30) and the mineralization marker osteocalcin (31). Immunohistochemical staining for F4/80 in sagittal long bone sections from 4-wk-old rapidly growing mice showed that F4/80 ϩ OsteoMacs formed a distinctive canopy-like structure over cuboidal osteoblast-like cells on bone surfaces (Fig.…”
Section: Osteomacs Are Associated With Sites Of Bone Modeling In Vivomentioning
confidence: 87%
“…The molecular mechanisms underlying this regenerative capacity are still largely unknown (11). Most investigations have focused on the underlying dura mater; however, this study investigated the age-related cellular and molecular differences between juvenile and adult primary osteoblast cultures and has shown a correlation between their states of proliferation, differentiation, and osteogenic potential in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the cellular and molecular differences between juvenile and adult dura mater, which are critical to calvarial bone induction. In contrast, few studies have investigated the effects of age on the cellular and molecular differences between juvenile and adult-derived calvarial osteoblasts (11).…”
mentioning
confidence: 97%